The case for inhibiting p38 mitogen-activated protein kinase in heart failure - Arabacilar, Pelin; Marber, Michael (Frontiers in Pharmacology, 2015)
This minireview discusses the evidence that the inhibition of p38 mitogen-activated protein kinases (p38 MAPKs) maybe of therapeutic value in heart failure. Most previous experimental studies, as well as past and ongoing clinical trials, have focussed on the role of p38 MAPKs in myocardial infarction and acute coronary syndromes. There is now growing evidence that these kinases are activated within the myocardium of the failing human heart and in the heart and blood vessels of animal models of heart failure. Furthermore, from a philosophical viewpoint the chronic activation of the adaptive stress pathways that lead to the activation of p38 MAPKs in heart failure is analogous to the chronic activation of the sympathetic, renin-aldosterone-angiotensin and neprilysin systems. These have provided some of the most effective therapies for heart failure. This minireview questions whether similar and synergistic advantages would follow the inhibition of p38 MAPKs.